2016
DOI: 10.1364/boe.7.005129
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy detects distant invasive brain cancer cells centimeters beyond MRI capability in humans

Abstract: Surgical treatment of brain cancer is limited by the inability of current imaging capabilities such as magnetic resonance imaging (MRI) to detect the entirety of this locally invasive cancer. This results in residual cancer cells remaining following surgery, leading to recurrence and death. We demonstrate that intraoperative Raman spectroscopy can detect invasive cancer cells centimeters beyond pathological T1-contrast-enhanced and T2-weighted MRI signals. This intraoperative optical guide can be used to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 31 publications
0
70
0
Order By: Relevance
“…All the Raman measurements were performed during brain tumour resections. 93 A detailed review on intra-operative Raman spectroscopy has been given by Brusatori et al 94 The use of body uids like blood plasma/serum, urine, tears etc. can pave way for a diagnostic method that is minimally invasive.…”
Section: Results and Discussion (I) Raman Spectroscopy Towards Biolomentioning
confidence: 99%
“…All the Raman measurements were performed during brain tumour resections. 93 A detailed review on intra-operative Raman spectroscopy has been given by Brusatori et al 94 The use of body uids like blood plasma/serum, urine, tears etc. can pave way for a diagnostic method that is minimally invasive.…”
Section: Results and Discussion (I) Raman Spectroscopy Towards Biolomentioning
confidence: 99%
“…Jermyn et al extended their previous intraoperative study and compared the Raman¯ndings with \T1-contrast-enhanced and T2-weighted MRI sequences", and reported that RS could detect cancer up to 3.7 cm for T1-contrast enhanced and 2.4 cm for T2 MRI boundary. 43 Recently, researchers from Canada have explored brain needle biopsy and used RS in the high wavenumber region to provide a proof of concept in human subject. 44 A summary of major studies carried out on animal models, ex vivo studies on human samples, and in vivo studies on human subjects are summarized in Table 1.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…61 The same type of superficial probe has been used for intraoperative brain cancer detection. [62][63][64] Using the fiber probe on 17 patients with WHO grade 2 to 4 gliomas, it was possible to accurately differentiate normal brain from dense cancer and normal brain invaded by cancer cells, with a sensitivity of 93% and a specificity of 91%. 64 The group around Mahadevan-Jansen used this probe to characterize human cervical remodeling throughout pregnancy 65 and inflammatory bowel disease (IBD).…”
Section: Basic Raman Probe Setupsmentioning
confidence: 99%
“…During brain surgery, a navigation attachment (Medtronic SureTrak) was used for spatial registration with the Medtronic StealthStation system, enabling MR guidance of measurement and tissue sample collection locations. 62,64 A commercial Raman probe from EMVision LLC was adapted to the ARAKNES 114 robotic platform and tested using tissue samples. The final intent is to identify ambiguous tissue margins during robot-assisted endoluminal surgeries.…”
Section: Image Guidancementioning
confidence: 99%